2017
DOI: 10.1016/j.ebiom.2017.08.014
|View full text |Cite
|
Sign up to set email alerts
|

Results of Use of Tissue-Engineered Autologous Oral Mucosa Graft for Urethral Reconstruction: A Multicenter, Prospective, Observational Trial

Abstract: BackgroundHarvest of oral mucosa for urethroplasty due to urethral stricture is associated with donor-site-morbidity. We assessed functionality and safety of an authorized tissue-engineered oral mucosa graft (TEOMG) under routine practice in stricture recurrences of any etiology, location, length and severity (real-world data).Methods99 patients from eight centers with heterogenous urethroplasty experience levels were included in this prospective, non-interventional observational study. Primary and secondary o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 30 publications
2
41
0
Order By: Relevance
“…A multicentre, prospective observational trial was performed in Germany in 2017 that investigated a tissue‐engineered oral mucosa graft (MukoCell) . The results of this study demonstrated a recurrent stricture rate of 33% at one year, which is consistent with the reported rates after use of native oral mucosa.…”
Section: Biomaterials (Scaffolds)supporting
confidence: 79%
“…A multicentre, prospective observational trial was performed in Germany in 2017 that investigated a tissue‐engineered oral mucosa graft (MukoCell) . The results of this study demonstrated a recurrent stricture rate of 33% at one year, which is consistent with the reported rates after use of native oral mucosa.…”
Section: Biomaterials (Scaffolds)supporting
confidence: 79%
“…Barbagli and Lazzeri concluded 'that by following strict protocol criteria, it is possible to move tissue-engineering technology from the laboratory bench to the bedside'. They did, however, emphasise the importance of an appropriate subsequent study and were justified in taking a cautious approach as the subsequent larger prospective observational multicentre clinical study of 99 patients from eight centres Subsequently showed from this group [39]. They reported success with a heavy reliance on subjective measures and flow rates at 2 years in 98 patients.…”
Section: Tissue Engineeringmentioning
confidence: 99%
“…Tissue engineering aims to develop in vitro tissues to improve or replace impaired biological tissues in vivo. To date, clinical applications of tissue engineering are limited to tissues which do not require vascularization nor anastomosis [ 1 , 2 , 3 , 4 ]. The 3D engineered tissues exceeding 200 µm (the effective diffusion limit of oxygen), which are densely populated with cells, quickly develop a necrotic core, if they are not vascularized [ 5 ].…”
Section: Introductionmentioning
confidence: 99%